2016
DOI: 10.1093/nar/gkw321
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule microscopy reveals mechanistic insight into RNA polymerase II preinitiation complex assembly and transcriptional activity

Abstract: Transcription by RNA polymerase II (Pol II) is a complex process that requires general transcription factors and Pol II to assemble on DNA into preinitiation complexes that can begin RNA synthesis upon binding of NTPs (nucleoside triphosphate). The pathways by which preinitiation complexes form, and how this impacts transcriptional activity are not completely clear. To address these issues, we developed a single molecule system using TIRF (total internal reflection fluorescence) microscopy and purified human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 62 publications
(57 reference statements)
1
23
0
Order By: Relevance
“…We also caution that our preferred model is based on data from one synthetic promoter containing multiple canonical core promoter elements, whereas in vivo PIC assembly could use diverse pathways, depending on the composition of promoter structures and the local chromatin environment. Using a complementary single-molecule in vitro assay system, Goodrich and colleagues (Horn et al 2016) reported recently that TBP-TFIIB-TFIIF-Pol II can form a stable quadruple complex capable of supporting transcription, consistent with a partial preassembly model. In the future, simultaneous monitoring of multiple protein factors binding to immobilized promoter DNA, particularly when coupled to real-time nascent RNA detection , should help clarify how prevalent such hypothetical preassembled complexes may be and their functional relevance for promoter-specific gene regulation.…”
Section: Discussionmentioning
confidence: 76%
“…We also caution that our preferred model is based on data from one synthetic promoter containing multiple canonical core promoter elements, whereas in vivo PIC assembly could use diverse pathways, depending on the composition of promoter structures and the local chromatin environment. Using a complementary single-molecule in vitro assay system, Goodrich and colleagues (Horn et al 2016) reported recently that TBP-TFIIB-TFIIF-Pol II can form a stable quadruple complex capable of supporting transcription, consistent with a partial preassembly model. In the future, simultaneous monitoring of multiple protein factors binding to immobilized promoter DNA, particularly when coupled to real-time nascent RNA detection , should help clarify how prevalent such hypothetical preassembled complexes may be and their functional relevance for promoter-specific gene regulation.…”
Section: Discussionmentioning
confidence: 76%
“…This step renders the DNA competent (DNA*) for PIC and EC formation, and probably represents binding to the core promoter of a subset of the RNApII general transcription factors. In particular, it is known that at least TBP and TFIIB must be present before RNApII can proceed on the pathway to PIC formation (2,41). Alternative simpler mechanisms lacking the non-productive RNApII binding intermediate (DNA·RNAPII) did not produce satisfactory agreement with the data.…”
Section: Quantitative Kinetic Model For Initiation Complex Formationmentioning
confidence: 88%
“…3B), and therefore conclude that Spt4/5 binding is confined to ECs, consistent with our mass spectrometry observations. The kinetics of RNApII basal transcription initiation (i.e., initiation that occurs in the absence of activators) has been previously examined in vitro, including by single-molecule methods (41,42,(44)(45)(46). Such studies typically observe transcription from only a small fraction of template molecules, although this can be greatly improved by pre-formation of PICs before initiating RNA synthesis (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human TBP, untagged TFIIB, TFIIF, and native human Pol II were prepared as described previously [20]. The ensemble in vitro transcription reactions were assembled as previously described [20]. Briefly, reactions were performed in 10% glycerol, Reactions were stopped and RNA transcripts were ethanol precipitated as described [16].…”
Section: Ensemble Transcription Assaysmentioning
confidence: 99%